Assessment of a planar inclusion in a solid cylinder. (February 2015) - Imran, M.; Eric Lim, S.F.; Putra, I.S.; Ariffin, A.K.; Tan, C.J.; Purbolaksono, J.
Highlights: Effect of crack eccentricity on the SIFs of an embedded crack. A crack aspect ratio determines the pattern and magnitude of the SIFs. Effect of crack inclination angle of a penny crack on all modes SIFs. Abstract: As a planar inclusion in a solid cylinder can lead to a catastrophic failure of a whole structure, relevant studies on evaluating quantitative fracture values are always sought for supporting the investigations. In line with the use of nondestructive evaluation technique for quantifying the embedded defects in structures, relevant research findings would be usable to contribute to the structural integrity analyses. It is also intended to have the possibility of the use of the data in a preliminary structural design stage. Since the complexity of the experimental setup for evaluating a planar inclusion in a solid component, numerical modeling is always desirable. There are currently very few available solutions of stress intensity factors for the embedded cracks in a solid cylinder in literature. In this work, the planar inclusion was considered as an embedded (penny/elliptical) crack. Stress intensity factors (SIFs) of an embedded crack for different crack aspect ratios, crack eccentricities and crack inclinations are presented. All the analyses were carried out by using a dual boundary element method (DBEM) based software.